Land use and land cover changes and their effect on ecosystem service values in the Bale Ecoregion, southeastern Ethiopia - Haileslassie, Amare; Taye, Meron Teferi; Diyessa, Merga; Mekuria, Wolde (Frontiers in Environmental Science, 2024)
Bale Ecoregion (BER) is known for its global importance in biodiversity and as a water tower for East African drylands. Land Use Land Covers (LULC) have been changing for decades and affecting forest Ecosystem Services Values (ESVs) but available information is limited. The present study addresses these gaps by using contrasting watersheds representing the highland, midland, and lowland agroecologies in BER. LULC classifications were performed using GIS-Remotesensing tools. Multisite imagery data (using Landsat image resolution 30mX30m) were generated for four observation periods : 1992, 2002, 2012, and 2022. A recently updated global Ecosystem Service Value (ESV) coefficient and the value transfer valuation method were applied to estimate the changes in ESVs related to LULC changes. The result demonstrates that between 1992 and 2022, forest land has declined by 3%, 63%, and 22% in the highland, midland, and lowland areas respectively. Different degrees of losses of ESVs were observed across the study periods and LULC. Of 21 specific ESVs investigated, the highest annual losses were recorded for water ecosystem services both in the midland and lowland landscape positions. Increased ESVs for cultivated land could not offset losses of food ESVs at the scale of agroecology. Significant impacts of LULC change on specific ecosystem services, such as water, and change in natural connectivity between the highland and lowland areas were observed. The result suggests that stakeholders need to co-plan and manage the BER. This evidence provides a scientific underpinning for understanding the connection between LULC change ESVs and supports informed policy decisions.